Epidemiological Description of COVID-19 Cases at selected Counties in Kenya that border Uganda and Tanzania, March-July 2020 - Gladys Mutethya Francis; Josephine Waihuini Ihahi; Adow Aden Buul; Florence Wanjiru Mugo; Robert Mburu Kuria; Kenneth Kipkoech Korir; Sora Jatani Biid; Julius Shem Otwabe; Ahmed Abade Mohamed; Waqo Boru; Elvis Omondi Oyugi; Maurice Omondi Owiny; et al. (Journal of Interventional Epidemiology and Public Health)
Introduction: World Health Organization (WHO) declared coronavirus disease of 2019 (COVID-19) a pandemic on March 11, 2020. By July 12, 2020, the cases had reached 12,552,765 globally with Kenya reporting 10,105 cases, a majority reported from counties hosting International Points of Entry (POEs). Transmission has continued across the border counties despite containment measures, thereby necessitating an epidemiological description of the cases to guide control measures.